New clothes for New Year's day - Bae, Hyun-Joo. (La Jolla, CA : Kane/Miller, 2007)
A young Korean girl looks forward to her family's New Year's celebration and the fancy clothes she will be wearing.
"Originally published as The New Year's best clothes"--Colophon.
Translated from the Korean.
Booklist
Horn Book
Wilson's Children
2.2
Keywords: Folklore -- Korea; New Year -- Folklore; Folklore -- Korea; New Year -- Folklore; Folklore -- Korea; New Year -- Folklore